High‐throughput sequencing of transposable element insertions suggests adaptive evolution of the invasive Asian tiger mosquito towards temperate environments - Clement Goubert; Helene Henri; Guillaume Minard; Claire Valiente Moro; Patrick Mavingui; Cristina Vieira; Matthieu Boulesteix (Molecular Ecology, 2017)
Invasive species represent unique opportunities to evaluate the role of local adaptation during colonization of new environments. Among these species, the Asian tiger mosquito, Aedes albopictus , is a threatening vector of several human viral diseases, including dengue and chikungunya, and raises concerns about the Zika fever. Its broad presence in both temperate and tropical environments has been considered the reflection of great “ecological plasticity.” However, no study has been conducted to assess the role of adaptive evolution in the ecological success of Ae. albopictu s at the molecular level. In the present study, we performed a genomic scan to search for potential signatures of selection leading to local adaptation in one‐hundred‐forty field‐collected mosquitoes from native populations of Vietnam and temperate invasive populations of Europe. High‐throughput genotyping of transposable element insertions led to the discovery of more than 120,000 polymorphic loci, which, in their great majority, revealed a virtual absence of structure between the biogeographic areas. Nevertheless, 92 outlier loci showed a high level of differentiation between temperate and tropical populations. The majority of these loci segregate at high insertion frequencies among European populations, indicating that this pattern could have been caused by recent adaptive evolution events in temperate areas. An analysis of the overlapping and neighbouring genes highlighted several candidates, including diapause, lipid and juvenile hormone pathways.

Isolation and gene flow: inferring the speciation history of European house mice - LUDOVIC DUVAUX; KHALID BELKHIR; MATTHIEU BOULESTEIX; PIERRE BOURSOT (Molecular Ecology, 2011)
Inferring the history of isolation and gene flow during species differentiation can inform us on the processes underlying their formation. Following their recent expansion in Europe, two subspecies of the house mouse ( Mus musculus domesticus and Mus musculus musculus ) have formed a hybrid zone maintained by hybrid incompatibilities and possibly behavioural reinforcement, offering a good model of incipient speciation. We reconstruct the history of their divergence using an approximate Bayesian computation framework and sequence variation at 57 autosomal loci. We find support for a long isolation period preceding the advent of gene flow around 200 000 generations ago, much before the formation of the European hybrid zone a few thousand years ago. The duration of the allopatric episode appears long enough (74% of divergence time) to explain the accumulation of many post‐zygotic incompatibilities expressed in the present hybrid zone. The ancient contact inferred could have played a role in mating behaviour divergence and laid the ground for further reinforcement. We suggest that both subspecies originally colonized the Middle East from the northern Indian subcontinent, domesticus settling on the shores of the Persian Gulf and musculus on those of the Caspian Sea. Range expansions during interglacials would have induced secondary contacts, presumably in Iran, where they must have also interacted with Mus musculus castaneus . Future studies should incorporate this possibility, and we point to Iran and its surroundings as a hot spot for house mouse diversity and speciation studies.

How sympatric is speciation in the Howea palms of Lord Howe Island? - WIESŁAW BABIK; ROGER K. BUTLIN; WILLIAM J. BAKER; ALEXANDER S. T. PAPADOPULOS; MATTHIEU BOULESTEIX; MARIE‐CHARLOTTE ANSTETT; CHRISTIAN LEXER; IAN HUTTON; VINCENT SAVOLAINEN (Molecular Ecology, 2009)
The two species of the palm genus Howea (Arecaceae) from Lord Howe Island, a minute volcanic island in the Tasman Sea, are now regarded as one of the most compelling examples of sympatric speciation, although this view is still disputed by some authors. Population genetic and ecological data are necessary to provide a more coherent and comprehensive understanding of this emerging model system. Here, we analyse data on abundance, juvenile recruitment, pollination mode and genetic variation and structure in both species. We find that Howea forsteriana is less abundant than Howea belmoreana . The genetic data based on amplified fragment length polymorphisms markers indicate similar levels of variation in the two species, despite the estimated census population size of H. belmoreana being three times larger than that of H. forsteriana . Genetic structure within species is low although some weak isolation by distance is detectable. Gene flow between species appears to be extremely limited and restricted to early‐generation hybrids – only three admixed individuals, classified as F2s or first generation backcrosses to a parental species, were found among sampled palms. We conclude that speciation in Howea was indeed sympatric, although under certain strict definitions it may be called parapatric.